PENGARUH PERSEPSI DAN RELIGIUSITAS MASYARAKAT TERHADAP SIKAP DAN MINAT SEDEKAH MENGGUNAKAN PEMBAYARAN NON TUNAI - Faridho, Muhammad Al; Rini, Dewi Wahyu Setyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study aims to determine the effect of community perception and religiosity towards the behavior and interest of alms use sedekah cashless. Research methods using quantitative approach. Data analysis using t test with smart application PLS version 3. The results of this study indicate the value of t test is less than 0.05. It was concluded that there was an influence of community perception and religiosity on alms behavior and interest using cashless. Keywords: perception; religiosity; behavior; interest; cashless